The Impression of Rhetorical Devices in Wendys Taglines - Apryanti Madah Munthe; Ria Lestari (Journal of Language and Literature, 2016)
Advertisements are able to attract and capture audiences attentions by means of words, phrases, or sentences as seen in Wendys taglines. This paper attempts ate finding out kinds of rhetorical devices used in the taglines and how the taglines impress the audiences attentions. There were 39 taglines used by Wendys since 1969. The findings show there are 19 kinds of rhetorical devices in the taglines: aphaeresis, parallelism, asyndeton, alliteration, assonance, anaphora, epanalepsis, homoioteleuton, rhyme, free verbal repetition, metaphor, hyperbole, litotes, onomatopoeia, rhetorical question, periphrasis, anthimeria, polysemy, and pun. From the audiences response, assonance is the most persuasive rhetorical device in the taglines. Keywords: taglines, rhetorical devices, Wendys taglines